General and Central Obesity Are Associated With Increased Severity of the VMS and Sexual Symptoms of Menopause Among Chinese Women: A Longitudinal Study - Tang, Ruiyi; Fan, Yubo; Luo, Min; Zhang, Duoduo; Xie, Zhuolin; Huang, Feiling; Wang, Yuchen; Liu, Gaifen; Wang, Yaping; Lin, Shouqing; Chen, Rong (Frontiers in Endocrinology, 2022)
Background: Strong evidence has linked overweight and obesity to increased risks of cardiovascular disease and all-cause mortality in Chinese populations. Menopause is considered associated with increased obesity and central body fat distribution. However, the correlation between obesity and menopausal symptoms has not been well studied. Objective: To examine the associations between obesity or abdominal obesity and menopausal symptoms as women progressed from premenopausal to postmenopausal status. Design: This study included 430 midlife Chinese women who had experienced natural menopause and were followed up for 10 years. Physical examinations and questionnaires should be completed annually. The questionnaires include the Menopause-Specific Quality of Life questionnaire, the Hospital Anxiety and Depression Scale, and other physical and behavioral factors. Results: Among women who were not obese (n=345) or not abdominal obese (n=372) at baseline, 5.8% and 31.7% became obese or abdominal obese at the recent follow-up visit, respectively. Women at the recent follow-up visit had an increased body mass index (BMI) by 0.14%, and the waist-to-hip ratio (WHR) increased by 5.2% compared with the data at baseline. In multivariate analysis, more frequent hot flashes, moderate/severe bothered vasomotor symptoms (VMS), mild bothered sexual functioning, and less anxiety symptoms were significantly associated with obesity. Increasing age, moderate/severe bothered VMS, and less anxiety symptoms were independently associated with abdominal obesity. Multivariable analysis also showed that less education level is independently associated with both obesity and abdominal obesity. Conclusion: Our findings suggest that the proportion of obesity and abdominal obesity increased gradually during menopause. The increase of abdominal obesity is more rapidly than obesity in middle-aged women. Both obesity and abdominal obesity are related with severe or frequent VMS and anxiety symptoms in Chinese women. Although the proportion of obese women in China is lower than in western countries, the problem of abdominal obesity and related complications cannot be ignored.